2003
DOI: 10.1111/j.1834-7819.2003.tb00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Pits and fissures: Relative space contribution in fissures from sealants, prophylaxis pastes and organic remnants

Abstract: Background: Previous studies by the authors have looked at the nature of the fissure system of human permanent molars and premolars, and has provided evidence for the presence of a prismless layer of enamel. It was noted during these studies that the fissure spaces were often occupied by material other than the fissure sealant. The aim of this study was to define these materials and to look at the percentage contribution of each to the sealed fissure space. Methods: A sample of teeth, both molars and premolars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…15, 16 The results of sealant retention, marginal adaptation and color matches in the present study corresponded to a previous study. 12 When sealant restoration was examined at 12 months, it was found that nanofilled sealant restoration showed acceptable retention, color matches as well as excellent marginal adaptation with the treated teeth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…15, 16 The results of sealant retention, marginal adaptation and color matches in the present study corresponded to a previous study. 12 When sealant restoration was examined at 12 months, it was found that nanofilled sealant restoration showed acceptable retention, color matches as well as excellent marginal adaptation with the treated teeth.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the nanoparticles preferentially scatter blue light, giving the restoration opalescent effects. 16 On the other hand, the particle size of microfilled resinmodified glass ionomer is ranged from 4.5 to 4.8 micrometers. 24 Low filler particles containing material is said to have good polishability as well as stability of the color.…”
Section: Discussionmentioning
confidence: 99%
“…This result was in agreement with previous reports. 8,9,[14][15][16] The results of SEM observation demonstrated that the debris-like smear layer was completely removed from the Carisolv-treated surfaces after acid-etching, and enamel prisms were exposed. These features were almost similar to the structure of the Carisolv-treated surfaces that have been previously described as flaky or irregular.…”
Section: Discussionmentioning
confidence: 99%
“…7 Possible reasons for this j o u r n a l o f d e n t i s t r y 3 6 ( 2 0 0 8 ) 1 3 0 -1 3 7 early loss include wear or fracture of sealant material, and presence of organic debris or unetched areas after routine cleaning. 8,9 Furthermore, microleakage of fissure sealants due to polymerization shrinkage, 10 insufficient material penetration, 11 saliva contamination 12 and sealant viscocity, 13 may also adversely affect the success of fissure sealing. The adhesive effect of fissure sealants depends on the mechanical bond strength between the enamel surfaces in a fissure groove and sealant materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation